The Role of Silicon in Antiherbivore Phytohormonal Signalling - Hall, Casey R.; Waterman, Jamie M.; Vandegeer, Rebecca K.; Hartley, Susan E.; Johnson, Scott N. (Frontiers in Plant Science, 2019)
The role of plant silicon (Si) in the alleviation of abiotic and biotic stress is now widely recognised and researched. Amongst the biotic stresses, Si is known to increase resistance to herbivores through biomechanical and chemical mechanisms, although the latter are indirect and remain poorly characterised. Chemical defences are principally regulated by several anti-herbivore phytohormones. The jasmonic acid (JA) signalling pathway is particularly important and has been linked to Si supplementation, albeit with some contradictory findings. In this Perspectives article, we summarise existing knowledge of how Si affects JA in the context of herbivory and present a conceptual model for the interactions between Si and JA signalling in wounded plants. Further, we use novel information from the model grass Brachypodium distachyon to underpin aspects of this model. We show that Si suppresses reduces JA concentrations in plants subjected to chemical induction (methyl jasmonate; MeJA) and herbivory (Helicoverpa armigera) by 34% and 32%, respectively. Moreover, +Si plants had 13% more leaf macro-hairs than –Si plants. From this study and previous work, our model proposes that Si acts as a physical stimulus in the plant which causes a small, transient increase in JA. When +Si plants are subsequently attacked by herbivores they potentially show a faster induction of JA due to this priming. +Si plants that have already invested in biomechanical defences (e.g. trichomesmacro-hairs), however, have less utility for JA-induced defences and show lower levels of JA-induction overall.